Utility of total lymphocyte count as a surrogate for absolute CD4 count in the adult Indian HIV population: A prospective study - Karanth, Suman S; Rau, N R; Gupta, Anurag; Kamath, Asha; Shanbhogue, Vikram; Pruthvi, B C (Avicenna Journal of Medicine, 2014)
Background: Standard methods of CD4 counts and plasma viral load estimation require specialized equipment, highly trained personnel and are extremely expensive. This remains a major challenge for the initiation of anti-retroviral therapy for patients in resource-limited settings. Objective: To assess the clinical utility of the total lymphocyte count (TLC) to serve as a surrogate marker for predicting a CD4 counts <350 cell/mm 3 in patients with HIV. Materials and Methods: A prospective study of 200 consecutive newly detected highly active anti-retroviral therapy (HAART) naïve HIV patients admitted over a one year period was conducted. Linear regression, Pearson correlation and receiver operating characteristic (ROC) curves were used to calculate the relationship between TLC and CD4 counts. Results: A significant correlation between TLC and CD4 count was observed (r = 0.682, P < 0.001). TLC cut off of 1200 cell/mm 3 as a predictor of CD4 count <350 cell/mm 3 had 73.1% sensitivity, 100% specificity, 100% positive predictive value (PPV) and 51.4% negative predictive value (NPV). Raising the cutoff to 1500 cells/mm 3 improved the sensitivity to 82.1% with 88.2% specificity, 96.5% PPV, 44.4% NPV. The ROC curve demonstrated highest area under curve (AUC = 0.8) for TLC of 1500 cell/mm 3 . Conclusion: The study showed that TLC cutoff value of 1500 cells/mm 3 was a cost effective surrogate marker for CD4 counts <350 cells/mm 3 in resource-limited settings.
Keywords: CD4 count; human immunodeficiency virus; surrogate marker; total lymphocyte count